Improving Students’ Writing Skill in Descriptive Text by Using Roundtable Technique - Fatmawati; Salija, Kisman; Baa, Sultan (Institut Agama Islam Negeri Palopo, 2025)
This research, which is a quasi-experiment, sought to ascertain whether using the Roundtable technique actually helped students improve their ability to write descriptive texts as well as to ascertain the students' perceptions of the technique's effectiveness. Implementing the Roundtable technique is the independent variable in this study, and students' perspectives and their abilities to write descriptive texts are the dependent variables. The population of this study consists of all six classes of SMK Tiwikrama Mamuju, and the sample consisted of class X1 as the experiment class and class X2 as the control class, both of which included 28 students each. The research data were obtained by giving a learning achievement test on the description text material in the form of pre-test and post-test. The data analysis technique is by using the SPSS program, data percentages and tables. Based on the results of statistical analysis, P = 0.00 less than a = 0.05. It is means that the implementation of the Roundtable Technique has a significant effect on the writing skills of X1 students of SMK Tiwikrama Mamuju on the subject matter of descriptive text.